Rare Malignancies in Eastern India, Socio-Economic Impact - Senapati, Surendranath (Rare Tumors, 2016)
The etiology of cancer is multifactorial. Various factors, including physical carcinogens, chemicals and viral carcinogens affect patients with known predisposing factors who subsequently develop malignancies. Here is a retrospective study of 18 patients who developed rare malignancies in clinical situations like xeroderma pigmentosum, tuberous sclerosis, neurofibromatosis, hereditary multiple exostosis, second malignancies due to radiotherapy and chronic irritation. The predisposing factors like chronic infection in leprosy, filariasis, poverty and ignorance leading to the chronicity of the lesion, lack of available health care facilities and socio-cultural background, i.e. consanguinity marriage in some community are responsible for the development of these rare malignancies. They were treated at A.H Regional Cancer Centre, Cuttack, Odisha, which is located at Eastern part of India for various malignancies, between January 1989 and January 2008. Malignancies that developed in patients with the above predisposing factors are being reported here due to their rarity and to highlight the impact of socio cultural background in developing these malignancies. Patients with above clinical situations should be kept under close observation for early detection of malignancy so their chances of survival can be improved. In addition, those oncogenic stimuli that initiated or propagated the malignancies, due to socio-economic factors, should be addressed promptly to prevent their eventual development.